Exercise electrocardiogram testing in two brothers with different outcome – a case study exercise testing in master cyclists - Rüst, Christoph Alexander (Dove Medical Press, 2013)
The cases of two brothers training and competing as master cyclists and both preparing for a cycling tour are presented. The older brother aged 66 years went first to the primary care physician and presented with an asymptomatic depression in the exercise stress test of the ST segment in V5 and V6 during recovery after complete exhaustion. Coronary angiography revealed a multi vessel coronary artery disease and he underwent bypass surgery. One year later, he successfully completed his planned cycling tour of ~600 km in seven stages and covering ~12,000 m of total ascent. The younger brother aged 59 years went a few months later to the primary care physician and also performed asymptomatic exercise stress testing without changes in the ST segments. Unfortunately, 2 months later he suffered a cardiac arrest during his cycling tour and survived following immediate successful cardiopulmonary resuscitation on the road by his cycling colleagues. Immediate invasive coronary arteriography showed a complete stenosis of the trunk of arteria coronaria sinistra (left coronary artery), a 40%–50% stenosis of ramus circumflexus, and a 20% stenosis of arteria coronaria dextra (right coronary artery). The left coronary artery was dilated and he continued cycling 2 months later. In both brothers, familial hypercholesterolemia was the main cardiovascular risk factor for the multi vessel coronary artery disease. A negative exercise electrocardiogram in siblings with an increased risk for coronary artery disease seemed not to exclude an advanced multi vessel coronary artery disease. In master athletes with asymptomatic exercise electrocardiogram but a positive family history, further examinations should be performed in order to detect relevant stenosis in coronary arteries.